Hard Anodize of 6061-T0 Aluminium Alloy in Sulfuric Acid Bath at Near Zero Temperature and Its Mechanical Properties - Ndaru Adyono; Wahyu Dwi Lestari (Future Science)
All articles must contain an abstract. The abstract text should be formatted using 10 point Times New Roman and indented 20 mm from the left margin. The abstract should give readers concise information about the content of the article and indicate the main results obtained and conclusions drawn. The abstract is not part of the text and should be complete in itself; no table numbers, figure numbers, references, or displayed mathematical expressions should be included. It should be suitable for direct inclusion in abstracting services and should not normally exceed 200 words in a single paragraph.